"Practical Monetarism" und Zentralbankkooperation: Die Bank of England und die britische EWS-Politik 1979-1990; "Practical Monetarism" and Central Bank Cooperation: The Bank of England and British EMS Policy 1979-1990 - Juliane Clegg (Vierteljahrschrift für Sozial- und Wirtschaftsgeschichte (VSWG), 2024)
– This article analyses the Bank of England's (BoE) involvement in UK policy towards the European Monetary System (EMS) between 1979 and 1990. It outlines how scepticism about rigid monetarist approaches influenced the institution's stance towards the EMS. Despite internal disagreements, the BoE supported Britain's entry into the EMS Exchange Rate Mechanism (ERM). Although there were government attempts to sideline it in high-level discussions, the BoE maintained its influence through its central role in European central bank cooperation and policy implementation. Increased involvement in European monetary policy from 1988 sparked nuanced debates about the BoE's policy role and central bank autonomy which became an important catalyst for the move towards operational independence in 1997.
Keywords: N14; N24; N44; 330; central bank; Bank of England; monetary policy; Great Britain; monetary system